Synthesis & Antimicrobial Evaluation of Open Chain of Organo–Selenium Compounds - Nagham .Mahmood .Aljamali (Al-Qadisiyah Journal of Pure Science, 2017)
The organo-selenium compounds are one of important organic compounds in synthesis of different compounds and as anti microbial .The target organo –selenium compounds [3-7] were synthesized from the reaction between diethyl malonate and 4-amino benzoyl chloride to produce compound [1] ,which is react with sodium hydrogen selenide to give corresponding sodium aroylselenide [2] ,which is react with one of aroyl derivatives as shown in scheme (1) to produce compounds [3-7].All the synthesized compounds have been investigated using different chemical techniques ,such as ,(C.H.N)-analysis , (H.NMR–spectra ,FT.IR–spectra ) , melting points and biological study.